CD24 is expressed in HNSCC and is correlated with a dampened immune response - Deborah C. Schubert; Marvin Hürter; Dimo Dietrich; Sebastian Strieth; Peter Brossart; Peter Altevogt; Christine Sanders; Glen Kristiansen (Oral Oncology Reports)
Purpose:: Recently, CD24 on tumor cells was identified as a phagocytic inhibitor contributing to an immunosuppressive tumor microenvironment via binding to Siglec-10 on macrophages. Head and neck squamous cell carcinoma (HNSCC) are highly immunogenic tumors, but little is known about the expression of CD24 in HNSCC. We aimed to evaluate the expression of CD24 and its binding partner Siglec-10 as well as the infiltration density of macrophages and CD8 positive T-cells. Material and methods: A previously described and characterized cohort of HNSCC (n = 156) was semiquantitatively analyzed by immunohistochemistry for CD24, Siglec-10, CD8, CD68, CD163 and CD80 expression. The expression data was correlated to clinico-pathological parameters. Results: CD24 was expressed in 81.6 % of cases, showing an inverse correlation with the CD68 and CD8 infiltration density, indicating an immunosuppressive feature of CD24. Also, CD24 expression was higher in HNSCC with a negative HPV status. Nodal positive HNSCC showed significantly increased infiltration density of CD68+ cells. Furthermore, the cell density of CD68 and CD163 positive cells was associated with HPV/p16 positive HNSCC. Conclusion: CD24 is commonly expressed in HNSCC and may contribute to an immunosuppressive tumor microenvironment in HNSCC. Its role as a putative therapy target should be clarified in further studies.